Alternative procedure for the cold test for soybean seeds (Scientia Agricola, 2010)
The growing demand for high quality soybean [Glycine max (L.) Merrill] seeds requires a precise seed quality control system from the seed industry. One way to accomplish this is by improving vigor testing. Cold test has been traditionally employed for corn seeds. However, it has also been used for other seed crops such as cotton (Gossypium spp.), soybean (Glycine Max), dry bean (Phaseolus vulgaris) and pea (Pisum sativum). This study was carried out with the objective of adjusting an alternative procedure for the cold test to determine soybean seed vigor. Six commercial soybean seed lots of the cultivar BRS 133 were used. The physiological potential of the seed lots was evaluated by germination on paper towel and sand box, seedling field emergence, tetrazolium, accelerated aging and electrical conductivity tests. Seed moisture content was also determined. The temperature used for the cold test procedures was 10ºC during five days. Four cold test procedures were evaluated: i) plastic boxes with soil; ii) rolled paper towel with soil; iii) rolled paper towel without soil, and iv) an alternative procedure, using rolled paper towel without soil under cold water. A completely randomized experimental design with eight replications was used and the means were compared by the Tukey test (p = 0.05). To verify the dependence between the alternative test and others single linear correlation was used. All cold test procedures had similar coefficients of variation (CV), highlighting that rolled paper towel with soil and the alternative procedure had the best performance, with an average of 94% and 93% normal seedlings and CV of 3.2% and 3.6%, respectively. The alternative procedure has satisfactory results for estimating soybean seed vigor, yielding consistent results compared to the traditional procedure.